2005
DOI: 10.1161/circulationaha.104.516963
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cardiac Expression of Tissue Inhibitor of Metalloproteinase-1 and Tissue Inhibitor of Metalloproteinase-2 Is Related to Cardiac Fibrosis and Dysfunction in the Chronic Pressure-Overloaded Human Heart

Abstract: Background-Alterations in the balance of matrix metalloproteinases (MMPs) and their specific tissue inhibitors (TIMPs) are involved in left ventricular (LV) remodeling. Whether their expression is related to interstitial fibrosis or LV dysfunction in patients with chronic pressure overload-induced LV hypertrophy, however, is unknown. Methods and Results-Therefore, cardiac biopsies were taken in 36 patients with isolated aortic stenosis (AS) and in 29 control patients without LV hypertrophy. Microarray analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
191
2
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 278 publications
(210 citation statements)
references
References 31 publications
8
191
2
6
Order By: Relevance
“…Biopsies of patients with pressure-overload and left ventricular (LV) hypertrophy due to severe aortic stenosis (n ϭ 8) and control CABG patients (n ϭ 6) without LV hypertrophy were collected and characterized as described (32). A primary antibody against KLF15 (generated by Zymed) was used for immunostaining.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Biopsies of patients with pressure-overload and left ventricular (LV) hypertrophy due to severe aortic stenosis (n ϭ 8) and control CABG patients (n ϭ 6) without LV hypertrophy were collected and characterized as described (32). A primary antibody against KLF15 (generated by Zymed) was used for immunostaining.…”
mentioning
confidence: 99%
“…A primary antibody against KLF15 (generated by Zymed) was used for immunostaining. Myocyte cross-sectional area was determined, and the relative surface area of KLF15-immunoreactivity was expressed as percentage immunoreactive area over total area, using a Zeiss Axioplan2 microscope, a 3CCD video camera (DXC-93OP, Sony), and KS300 software as described (32). Immunocytochemistry and FACS Analysis.…”
mentioning
confidence: 99%
“…Among the four TIMPs identified to date, TIMP-2 is unique in that it activates pro-MMP-2 to active MMP-2 and also inhibits the active MMP-2. It was demonstrated that the expression of TIMP-1 and TIMP-2 increased significantly in chronic pressure-overloaded human hearts (Heymans et al, 2005b). When TIMP-1 was knocked out, mice suffered spontaneous LV dilatation, thus indicating the importance of the control of cardiac MMP activity by TIMP-1 (Roten et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Rats were followed by serial echocardiography at 10, 12, 15, 16, 18, 19, and 21 wk of age and killed at 15-18 wk upon clinical signs of HF (HF-prone/ HF-prone rats) or at 21 wk when clinical signs of failure had not appeared (compensated/compensated rats). Total RNA was isolated from LV biopsies and amplifi ed as described previously (10,25), hybridized to Aff ymetrix rat RAE230 2.0 GeneChips, and analyzed with Microarray Analysis Suite software (version 5.0). 50 μg of LV protein extracts were immunoblotted with polyclonal rabbit anti-LIMP-2 (1:500; Novus Biologicals) and polyclonal rabbit anti-GAPDH (1:10,000; Abcam).…”
Section: Methodsmentioning
confidence: 99%